2013
DOI: 10.1007/s00253-013-4918-6
|View full text |Cite
|
Sign up to set email alerts
|

Dengue virus tetra-epitope peptide expressed in lettuce chloroplasts for potential use in dengue diagnosis

Abstract: Dengue virus causes about 100 million cases of dengue disease per year in the world. Laboratory diagnosis is done mainly by serological techniques, which in many cases use crude virus extracts that may cause cross-reactions to other flaviviruses. These undesirable cross-reactions can be reduced or eliminated by using recombinant proteins based on restricted epitopes. Aiming to decrease flaviviral cross-reactions and non-specific interactions in dengue serological assays, a plant expression system was chosen fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Therefore, edible leafy vegetables are ideal for biopharmaceutical applications. The lettuce chloroplast system has been successfully used to express a number of vaccines and biopharmaceuticals (Boyhan and Daniell, 2011;Davoodi-Semiromi et al, 2010;Kanagaraj et al, 2011;Maldaner et al, 2013). Chloroplasts permit high gene expression levels and facilitate several post-translational modifications that are required for bioactivity such as pentamer assembly, disulphide bond formation, cyclization, protein lipidation and N-terminal methionine excision, but glycosylation does not occur in chloroplasts (Boyhan and Daniell, 2011;Davoodi-Semiromi et al, 2010;Kohli et al, 2014;Kwon et al, 2013a;Scotti et al, 2012;Sherman et al, 2014;Shil et al, 2014;Verma et al, 2010).…”
Section: Chloroplast Transformation Systemmentioning
confidence: 99%
“…Therefore, edible leafy vegetables are ideal for biopharmaceutical applications. The lettuce chloroplast system has been successfully used to express a number of vaccines and biopharmaceuticals (Boyhan and Daniell, 2011;Davoodi-Semiromi et al, 2010;Kanagaraj et al, 2011;Maldaner et al, 2013). Chloroplasts permit high gene expression levels and facilitate several post-translational modifications that are required for bioactivity such as pentamer assembly, disulphide bond formation, cyclization, protein lipidation and N-terminal methionine excision, but glycosylation does not occur in chloroplasts (Boyhan and Daniell, 2011;Davoodi-Semiromi et al, 2010;Kohli et al, 2014;Kwon et al, 2013a;Scotti et al, 2012;Sherman et al, 2014;Shil et al, 2014;Verma et al, 2010).…”
Section: Chloroplast Transformation Systemmentioning
confidence: 99%
“…In the present study, we have successfully expressed the tetravalent antigen in chloroplasts of the edible crop lettuce, assayed its stability upon passage through the gastrointestinal tract and determined its antigenicity in experimental animals. Further efforts in producing other dengue antigens in plants have also been reported (Kanagaraj et al ., ; Maldaner et al ., ). Our work adds to a growing number of studies in plant molecular farming that have demonstrated that production of vaccines and antibodies in plants is a very attractive alternative to traditional production systems.…”
Section: Discussionmentioning
confidence: 97%
“…Since the first report of transplastomic lettuce plants, the evaluation of different integration sites and transformation strategies have led to the successful expression of several recombinant proteins in lettuce plastids (Boyhan and Daniell, 2011;Davoodi-Semiromi et al, 2010;Ichikawa et al, 2010;Kanagaraj et al, 2011;Kanamoto et al, 2006;Maldaner et al, 2013;Ruhlman et al, 2007). Most importantly, lettuce is the only system so far that has been shown to be feasible for commercial scale production of clinical grade biopharmaceuticals (Su et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Several plant transient expression rely on viral vector systems. In the 1990s scientists were using Dengue virus tetraepitope peptide (cE-DI/IIp) Tobacco psbA promoter/ pRL1001 Lettuce plastid transformation Maldaner et al (2013) Agrobacterium to do transient expression in plants which does not rely on viral vectors (Kapila et al 1997). The study of plant viruses revealed their latent ability to carry foreign genes.…”
Section: Strategies To Enhance Transient Recombinant Protein Expressimentioning
confidence: 99%